Comparison of Er:YAG Laser and Ultrasonic Scaler in the Treatment of Moderate Chronic Periodontitis: A Randomized Clinical Trial - Birang, Reza; Yaghini, Jaber; Nasri, Naeimeh; Noordeh, Nasim; Iranmanesh, Pedram; Saeidi, Alireza; Naghsh, Narges (Journal of Lasers in Medical Sciences, 2017)
Introduction: Periodontitis is an inflammatory periodontal disease that leads to tooth loss. Recently laser has been introduced as an alternative treatment for periodontitis. The aim of the present study was to compare the effect of Erbium-doped Yttrium Aluminum Garnet (Er:YAG) laser with ultrasonic scaler in patients with moderate chronic periodontitis. Methods: In this randomized single-blind clinical trial, 27 patients with moderate chronic periodontitis were selected. One quadrant of the patients was treated by Er:YAG laser and the other one by ultrasonic scaler. Clinical parameters, including periodontal pocket depth (PPD), papillary bleeding index (PBI) and clinical attachment level (CAL) were measured before, as well as 6 and 12 weeks after treatment. Data were analyzed by SPSS 20 software using Friedman test, paired t test, independent t test and Mann-Whitney test. The significance level was set at 0.05. Results: The means of clinical parameters in both groups were significantly improved in the first and second follow-ups (P < 0.001). Although the means of PPD, PBI and CAL were slightly higher in the laser group than in the ultrasonic group, the differences were not statistically significant between these two groups (P > 0.05). Conclusion: Although both ultrasonic scaler and Er:YAG laser could effectively improve clinical periodontal parameters, the results did not reveal the superiority of Er:YAG laser over ultrasonic scaler or vice versa.